Simulation solvent extraction of rare earth metal source origin from marine sediment - Ahmat, Farouq; Mohd Yusri, Mohd Yunus; Nurul Ain, Ismail (IOP Publishing Ltd., 2021)
Ocean mining probably one of the world's largest untapped resources of rare earth elements. Specifically, the rare earth resources from polymetallic nodule which receive less attention from industry due to the various challenges. This article studied the simulation HDEHP-HCl system fractional cascade extraction strategy for extraction of rare earth elements from polymetallic nodule. HDEHP-HCl was capable of complete extract very high purity rare earth elements (99.9%). The fractional cascade extraction strategy simulation designed for the separation of rare earth elements could be momentous for practical application. The simulation data shows high purity of products at both outlets, aqueous and organic are obtainable. All these will provide the promising industrial applications of HDEHP-HCl system in extracting rare earth elements from polymetallic nodule with more fundamental data and guidance.